Tree-structure Extraction Algorithm for Accurate and Robust Skeletons - Sato, Mie; Nakajima, Masayuki; Bender, Michael A.; Kaufman, Arie E.; Bitter, Ingmar (The Journal of The Institute of Image Information and Television Engineers, 2000)
An algorithm is described for extracting tree-structure skeletons that are accurate and robust. Volumetric skeletons are needed to accurately measure the length along branching and winding structures. Skeletons are also needed for automatic virtual navigation, such as traveling through human organs to control the movement and orientation of a virtual camera. The proposed algorithm finds the skeleton accurately and rapidly. The solution is automatically obtained, freeing the user from having to engage in preprocessing the data. Accurate skeletons were computed on a number of test datasets, and t he algorithm was demonstrated to be efficient with running times of below five minutes.